How happy is healthy enough? Uncovering the happiness threshold for global non-communicable disease prevention - Iuga, Iulia Cristina; Jafri, Syeda Rabab; Iuga, Horia (Frontiers in Medicine, 2025)
ObjectivesTo determine whether the relationship between subjective wellbeing (happiness) and premature mortality from non-communicable diseases (NCDs) is non-linear and to identify the happiness level at which population health gains are maximized.MethodsA balanced panel of 123 countries (2006-2021) was analyzed. A Panel Smooth Transition Regression (PSTR) model examined the effect of national Life-Ladder scores on the 30-to-70-year NCD mortality rate, controlling for alcohol consumption, obesity prevalence, urbanization, PM2.5 exposure, health expenditure, GDP per capita and governance quality. The Life-Ladder index served as the transition variable, allowing coefficients to vary across two regimes separated by an estimated threshold. Dynamic feedback was explored with panel Vector-Autoregression (VAR) and impulse-response analysis.ResultsThe model identified a single threshold at 2.7 Life-Ladder points and rejected parameter constancy (LM-F = 8.85, p < 0.001). Above this level, each 1% rise in happiness decreased NCD mortality by 0.43% (p < 0.001); below it, the effect was nil. Obesity and alcohol consistently raised deaths, whereas urbanization turned from harmful to protective in the high-happiness regime. Health spending remained protective, and GDP per capita mattered only beyond the threshold. Complementary VAR and impulse-response analyses confirm a bidirectional negative linkage between happiness and NCD mortality and show that obesity, alcohol use and air pollution remain positive drivers of deaths. PVAR confirmed bidirectional Granger causality between happiness and NCD mortality and showed that a positive happiness shock elicits a sustained downward mortality response with no sign reversal.ConclusionSubjective wellbeing (happiness) appears to function as a population health asset only once a minimum threshold of 2.7 (on the 0–10 Life Ladder scale) is surpassed. Beyond this point, higher levels of happiness are associated with progressively lower NCD mortality, with no evidence within the observed range of adverse effects from “excessive” happiness. Public health strategies that elevate wellbeing above this tipping point-while concurrently addressing obesity, alcohol consumption, and environmental hazards-may initiate a reinforcing cycle of improved happiness and extended, healthier lifespans.